Odpowiedź :
Odpowiedź:
a)
– 3x+5 = 17
-3x = 17 - 5 /:(-3)
x = -12/3 = -4
b)
3(1 - x) +2 = -7
3 - 3x + 2 = -7
-3x = -7 - 5 /:(-3)
x = 12/3 = 4
c)
3 (0,4x + 1,2)-2 (0,3x – 2,6)= 0,1x
1,2x + 3,6 - 0,6x + 5,2 = 0,1x
0,6x - 0,1x = -8,8
0,5x = -8,8 /:0,5
x = -8,8/0,5 = -17,6
d)
3x ( 2x+5)= (x + 3) (6x+1)
6x² + 15x = 6x² + x + 18x + 3
6x² - 6x² + 15x - 19x = 3
-4x = 3 /:(-4)
x = -3/4
e)
2x+44=12x+1
2x - 12x = 1 - 44
-10x = -43 /:(-10)
x = 4,3
Szczegółowe wyjaśnienie:
Odpowiedź:
a) – 3x+5 = 17 | - 5
-3x=12 | : 3
-x= 4
x = 4
b) 3(1 - x) +2 = -7
3 - 3x + 2 = -7
5 - 3x = -7 | - 5
- 3x = - 12 | : (-3)
x = 4
c) 3 (0,4x + 1,2)-2 (0,3x – 2,6)= 0,1x
1,2x + 3,6 - 0,6x + 5,2 = 0,1x
0,6x + 8,8 = 0,1x | -0,6x
8,8 = -0,5x | : (-0,5)
-17,6 = x
d) 3x ( 2x+5)= (x + 3) (6x+1)
6x² + 15x = 6x² + x + 18x + 3
6x² + 15x = 6x² + 19x + 3 | -6x²
15x = 19x + 3 | - 19x
-4x = 3 | : (-4)
x = - 3/4 (ułamek)
e) 2x+44=12y+1 | - 44
2x = 12y - 43 | : 2
x = (12y−43):2 lub można to zapisać w ułamku 12y - 43/2
Mam nadzieję, że pomogłam (;